An analysis of the quality of 1920s dresses from a university collection. Issue 1 (1st December 2014) - Saiki, Diana; Stephens, Gary
The purpose of this study was to analyse eveningwear dresses from the 1920s in a university collection with a quality framework often used by university classes for examining contemporary clothing. The method provided an in-depth analysis identifying critical features of garments from the 1920s and information about the state of ready-to-wear in the 1920s worn in a small town. Exploring application of curricular concepts provides new approaches to examining textiles and apparel in research and curation.